Properties of green particleboard made with citric acid, furfuryl alcohol and palm oil - Cher, Jia Dong (2019)
The diversification of the production of wood panel products such as particleboards is crucial as it affects the wood industry and furniture industry in terms of their operations. The consumption of UF has increased gradually and has been widely utilized for producing wood composites recently. As the awareness of society towards the environmental and human health issues is in demand, thus it is important to create a particleboard with natural binding agent in order to substitute the use of UF which acts as the main adhesives in the boards. The aims of this study were proposed to produce green particleboard with very low formaldehyde emission, good biological durability and acceptable physical properties. Subsequent to this, the physical properties such as thickness swelling and water absorption of the particleboard bonded with citric acid were determined. Also, the biological durability against white rot fungi and subterranean termites of the particleboard bonded with citric acid were investigated and the formaldehyde emission from particleboard bonded with citric acid was evaluated. In this study, it is proven that the production of particleboard bonded citric acid with the addition of 20% palm oil and 20% furfuryl alcohol could act as the green binder for substituting UF. Furthermore, the citric acid which is known as the main material of wood adhesive has been justified and examined throughout a series of properties evaluation.